2021
DOI: 10.1037/pspi0000253
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence and cooperation in daily life.

Abstract: Philosophers and scientists have long debated the nature of human social interactions and the prevalence of mutual dependence, conflict of interests, and power asymmetry in social situations. Yet, there is surprisingly little empirical work documenting the patterns of interdependence that people experience in daily life. We use experience sampling to study how people think about three dimensions of interdependence in daily life and how these dimensions relate to cooperation. In Study 1, 139 romantic couples (n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 143 publications
4
96
0
Order By: Relevance
“…So far, relationship science has given much emphasis to partners’ behaviors, but partners’ actions are strongly tied to the situations that they experience. For example, while it may be very easy to behave in a trustworthy manner in situations of corresponding interests, it may be way more challenging to do so in situations of conflict of interests [ 27 , 33 ]. Interdependence theory [ 13 , 25 ] provides the ideal framework to investigate how the properties of social situations that partners experience shape relationship dynamics and dispositions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…So far, relationship science has given much emphasis to partners’ behaviors, but partners’ actions are strongly tied to the situations that they experience. For example, while it may be very easy to behave in a trustworthy manner in situations of corresponding interests, it may be way more challenging to do so in situations of conflict of interests [ 27 , 33 ]. Interdependence theory [ 13 , 25 ] provides the ideal framework to investigate how the properties of social situations that partners experience shape relationship dynamics and dispositions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we assessed each person’s perception of their interdependent situation with their partner, rather than the objective situation that the couple confront. However, previous research has shown that such perceptions tend to track objective features of reality, so there typically is a correspondence between the objective situation and the perceived one [ 26 , 27 ]. Yet it is the subjective construal of the situation, rather than its objective features, that should exert a strong influence on people’s emotions, cognitions, and behavior [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations